Study on metabolites of Bacillus producing soy sauce‐like aroma in Jiang‐flavor Chinese spirits. Issue 1 (25th November 2019) - Zhao, Xingxiu; Liu, Yuanhao; Shu, Li; He, Yiguo
Abstract: Jiang‐flavor Chinese spirits are one of the four basic liquor types in China. It has thousands of years of history in China and is widely enjoyed because of its unique flavor and broad application. Although Jiang‐flavor Chinese spirits have a unique soy sauce flavor, the associated key compounds and production mechanism remain unknown. To investigate this process, soy sauce flavor‐producing strains were obtained, and their metabolites were evaluated. Using wheat as the fermentation medium, we observed changes in total acid, amino nitrogen, and reducing sugar in three strains of Bacillus cerberus with high yield of tetramethylpyrazine during the fermentation process. The results showed that total acid and amino nitrogen contents increased and reducing sugars decreased in a time‐dependent manner. Additionally, detection of volatile compounds via solid‐phase microextraction and gas chromatography–mass spectrometry that total pyrazine content reached 43.175%, 50.461%, and 45.955% in wheat fermentation medium fermented by strains Q1, Q2, and Q5, respectively, suggesting that this important flavor compound might be related to the flavor of soy sauce. Moreover, we found that fermentation time was an important factor in soy sauce flavor, as volatile compounds were detected at different times by the three strains, with pyrazines not detected before 48 hr and peaking at 50.461% after 144 hr. These results indicated that strain Q2 exhibited optimal fermenting performance and might be useful for fermentation of Jiang‐flavor Chinese spirits. Abstract : Although Jiang‐flavor Chinese spirits have a unique soy sauce flavor, the associated key compounds and production mechanism remain unknown. To investigate this process, soy sauce flavour‐production strains were obtained, and their metabolites were evaluated.